Extracellular Vesicles Are Associated With Outcome in Veno-Arterial Extracorporeal Membrane Oxygenation and Myocardial Infarction - Siegel, Patrick M.; Bender, Ileana; Chalupsky, Julia; Heger, Lukas A.; Rieder, Marina; Trummer, Georg; Wengenmayer, Tobias; Duerschmied, Daniel; Bode, Christoph; Diehl, Philipp (Frontiers in Cardiovascular Medicine, 2021)
Background: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is being increasingly applied in patients with circulatory failure, but mortality remains high. An inflammatory response syndrome initiated by activation of blood components in the extracorporeal circuit may be an important contributing factor. Patients with ST-elevation myocardial infarction (STEMI) may also experience a systemic inflammatory response syndrome and are at risk of developing cardiogenic shock and cardiac arrest, both indications for VA-ECMO. Extracellular vesicles (EV) are released by activated cells as mediators of intercellular communication and may serve as prognostic biomarkers. Cardiomyocyte EV, released upon myocardial ischemia, hold strong potential for this purpose. The aim of this study was to assess the EV-profile in VA-ECMO and STEMI patients and the association with outcome. Methods: In this prospective observational study, blood was sampled on day 1 after VA-ECMO initiation or myocardial reperfusion (STEMI patients). EV were isolated by differential centrifugation. Leukocyte, platelet, endothelial, erythrocyte and cardiomyocyte (caveolin-3+) Annexin V+ EV were identified by flow cytometry. EV were assessed in survivors vs. non-survivors of VA-ECMO and in STEMI patients with normal-lightly vs. moderately-severely reduced left ventricular function. Logistic regression was conducted to determine the predictive accuracy of EV. Pearson correlation analysis of EV with clinical parameters was performed. Results: Eighteen VA-ECMO and 19 STEMI patients were recruited. Total Annexin V+, cardiomyocyte and erythrocyte EV concentrations were lower (p ≤ 0.005) while the percentage of platelet EV was increased in VA-ECMO compared to STEMI patients (p = 0.002). Total Annexin V+ EV were increased in non-survivors of VA-ECMO (p = 0.01), and higher levels were predictive of mortality (AUC = 0.79, p = 0.05). Cardiomyocyte EV were increased in STEMI patients with moderately-severely reduced left ventricular function (p = 0.03), correlated with CK-MBmax (r = 0.57, p = 0.02) and time from reperfusion to blood sampling (r = 0.58, p = 0.01). Leukocyte EV correlated with the number of coronary stents placed (r = 0.60, p = 0.02). Conclusions: Elevated total Annexin V+ EV on day 1 of VA-ECMO are predictive of mortality. Increased cardiomyocyte EV on day 1 after STEMI correlate with infarct size and are associated with poor outcome. These EV may aid in the early identification of patients at risk of poor outcome, helping to guide clinical management.